Using action research for curriculum development and improving the learning experience: A case study - Oksiutycz, A.; Azionya, C. (South African Journal of Higher Education, 2017)
ABSTRACT The need to bridge the gap between theory and praxis has necessitated the inclusion of context-based knowledge in university education that reflects the complexity of real life and grapples meaningfully with real world challenges. This has led to the inclusion of authentic learning practices in curricula and an appliaction of new teaching methods to achieve high quality learning, characterised by relevance to students and their future work environments. This paper discusses the action research which became a fundation for developing an applied module for a new Strategic Communication degree at a South African university. The objective of the project was to ensure that the course provides relevant skills and competencies, creates opportunities for the application of disciplinary knowledge within a social context and enhances the student’s learning experience by using project-based teaching. This reflective process culminated in the development of a curriculum for the applied second year modules in the BA Strategic Communication degree.